The Resident patient - Doyle, Arthur Conan; Granada Television ([United Kingdom Granada, 1985)
When a Russian father and son disappear during a consultation with the doctor, Holmes is called in to find out why the doctor's benefactor is now the most frightened man in town.
Information from LC database.
VHS
Producer, Michael Cox ; director, David Carson.
Jeremy Brett, David Burke, Patrick Newell.
Keywords: Holmes, Sherlock (Fictitious character).; Feature films; Crime; Mystery